Triangular gold nanoplates/two-dimensional nano mica platelets with a 3D lightning-rod effect as flexible nanohybrid substrates for SERS bacterial detection - Chen, Yan-Feng; Chang, Wen-Ru; Lee, Chia-Jung; Chiu, Chih-Wei (Journal of materials chemistry. B, Materials for biology and medicine, 2022)
Triangular gold nanoplates (TAuNPs) were prepared by a one-step rapid growth method and then reduced and stabilized on two-dimensional nano mica nanoplatelets (NMPs). We also prepared TAuNP/NMP nanohybrids with a three-dimensional lightning-rod effect by oxidative etching. The surface of the delaminated NMPs (only 1 nm thick) is highly charged and can provide a large specific surface area; thus, it can be used as a substrate for the stable growth of gold nanoplates. In addition, by controlling relevant synthesis parameters, the edge length of the TAuNPs can be easily adjusted in the range of 30-90 nm. During reduction of the TAuNPs, the cationic surfactant cetyltrimethylammonium chloride was added as a protective agent to surround the TAuNPs; consequently, the surface was positively charged, which facilitates adsorption for detecting molecules with negative charges. When nanohybrids were used in surface-enhanced Raman spectroscopy (SERS) to detect adenine molecules, the limit of detection concentration was 10 −9 M. The Raman enhancement factor was 5.7 × 10 7 , and the relative standard deviation (RSD) was 9.8%. Finally, this method was applied to the biological detection of Staphylococcus aureu s, and the surface charge and hydrophilic properties of the material significantly improved the SERS signal of S. aureus . The limit of detection concentration was 10 2 CFU mL −1 , and the RSD was 11.2%. The TAuNP/NMP nanohybrids can provide very rapid and sensitive SERS detection of biomolecules. Triangular gold nanoplates (TAuNPs) were prepared by a one-step rapid growth method and then reduced and stabilized on two-dimensional nano mica nanoplatelets (NMPs).